Design and optimisation of a footfall energy harvesting system - Gilbert, James M.; Balouchi, Farouk (Journal of intelligent material systems and structures, 2014)
The scavenging of electrical energy from normal human activity has a number of attractions, and footfall energy is seen as one of the most attractive sources. However, footfall motion is characterised by relatively large forces and low velocities, and this makes it inherently poorly matched to electromagnetic generators which operate most efficiently at high speeds. In order to achieve an efficient velocity amplification, a novel mechanism has been developed which makes use of a spring and flywheel as energy storage elements and a ‘striker’ mechanism which controls energy storage and release. This energy harvesting mechanism is capable of being used either in footwear or under a floor. In this article, the structure of the proposed mechanism is described; the optimisation of the system parameters, based on a dynamic model, is discussed; and experimental results for an under-floor system are presented.
Keywords: Mechanical Engineering; General Materials Science